Influencing factors of switching intention from cash to mobile payments - Wijaya, Legina Halim; Berlianto, Margaretha Pink (Institute of Computer Science (IOCS), 2025)
The use of technology has now been widely adapted to various human activities, one of which is in the payment process which currently uses a lot of technological innovation. This study objectives is to specify which factors that are considered to be able to influence the Switching Intention of visitors to XYZ Park in Cikarang in changing the habit of paying using cash by paying using mobile. This study is included in correlational research which is shown to determine the factors that influence a dependent variable. In this study, the population used was visitors to XYZ Park in Cikarang with a total of 263 respondents. Based on the result of the tests that have been carried out, it is known that the result produced by this study are Alternative Attractiveness, Inertia, and Monetary Value are proven to influence Switching Intention, while the variables Trust and Perceived of Security and Privacy do not have an effect on Switching Intention. Also, it is also known that Trust is an endogenous variable which is proven to be affected by Perceived Benefit and Perceived Risk. Also, Switching Costs is proven do not affect Inertia and Traditional Payment Habit is proven to affect Inertia